Continuous ECG Monitoring in Patients With Acute Coronary Syndrome or Heart Failure: EASI Versus Gold Standard. (May 2018) - Lancia, Loreto; Toccaceli, Andrea; Petrucci, Cristina; Romano, Silvio; Penco, Maria
The purpose of the study was to compare the EASI system with the standard 12-lead surface electrocardiogram (ECG) for the accuracy in detecting the main electrocardiographic parameters (J point, PR, QT, and QRS) commonly monitored in patients with acute coronary syndromes or heart failure. In this observational comparative study, 253 patients who were consecutively admitted to the coronary care unit with acute coronary syndrome or heart failure were evaluated. In all patients, two complete 12-lead ECGs were acquired simultaneously. A total of 6, 072 electrocardiographic leads were compared (3, 036 standard and 3, 036 EASI). No significant differences were found between the investigate parameters of the two measurement methods, either in patients with acute coronary syndrome or in those with heart failure. This study confirmed the accuracy of the EASI system in monitoring the main ECG parameters in patients admitted to the coronary care unit with acute coronary syndrome or heart failure.